Efficient numerical model for progressive collapse analysis of prestressed concrete frame structures. (November 2021) - Feng, De-Cheng; Shi, Hai-Rong; Parisi, Fulvio; Brunesi, Emanuele; Wang, Chun-Lin
Highlights: An efficient numerical model is developed for PC structures under progressive collapse. The model achieves a balance between efficiency and accuracy and captures both the global and local responses. Bonded PC structures exhibit greater progressive collapse resistance than unbonded ones. Effective prestress has limited influences on the progressive collapse behavior of PC structure. PC sub-assemblages with straight tendon profile have better performance and different failure modes. Abstract: Prestressed concrete (PC) frames are becoming an attractive solution for building structures due to the lightweight, aesthetics, and high resistance of their structural members. Nonetheless, few experimental and numerical studies have been carried out to investigate the progressive collapse resistance of PC frame structures, which is a key capacity feature to withstand extreme events. In this paper, a numerical model is proposed for progressive collapse analysis of PC beam-column sub-assemblages. The model was developed in OpenSees finite element software, simulating frame members via fiber beam-column elements, prestressing tendons (PTs) through corotational truss elements, the bond-slip behavior at the beam-column joint by zero-length elements, and coupling between the reinforced concrete beam and the PTs through kinematic compatibility conditions. The proposed modeling approach was validated through simulation of seven previously tested sub-assemblages under middle column removal. Numerical results indicate that the model allows a satisfactory simulation of vertical load–displacement pushdown curves, horizontal reaction–displacement curves, as well as local behaviors (e.g., rebar slip and fracture). Furthermore, a parametric study was conducted based on the validated numerical model to analyze the influence of effective prestress, tendon-concrete bond behavior, and tendon profile on the progressive collapse performance of PC sub-assemblages.